Perfectionism, Endorsement, and Retirement: A Note on "Working Retirees?" - Intropi, Pietro (Ethical theory and moral practice, 2025)
Should retirees be allowed to work? Should working imply forfeiting one’s retiree status? Are retirement and work incompatible? Manuel Valente has recently shown that distinguishing between leisure and free time has significant implications for thinking about retirement. Valente argues that, whilst it may be intuitive to think of retirement in terms of leisure (work-freeness), liberals would better think of retirement as free time (control over one’s time). Hence, working retirees is not an oxymoron. In this comment to Valente’s article I question whether perfectionism grounds a reason to protect free time, as Valente understands the concept. I also suggest that Valente’s claim that liberals should care about free time finds further support in a hybrid view of wellbeing that appeals to endorsement.